Evaluasi Sistem Informasi Manajemen pada Laporan Pemakaian dan Lembar Permintaan Obat di Puskesmas X - Mera Putri Pratitis; Jason Merari Peranginangin; Ika Purwidyaningrum (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
The required elements in drug procurement are usage and drug requisition report or Laporan Pemakaian dan Lembar Permintaan Obat (LPLPO). The application of the Management Information System (MIS) at X Public Health Center cannot fulfill the function of preparing the LPLPO, so it has an impact on the planning and procurement of the drug. This study aims to evaluate and determine the design of MIS development of LPLPO at X Public Health Center, Surakarta City. The study is a qualitative descriptive study with inductive analysis. The sampling in this study is a purposive sampling. The sample in this study were officers who operated SIM both pharmacists and assistant pharmacists for at least 1 year. This research was conducted at X Public Health Center Surakarta City in September-October 2021. The design of the system in this study uses the prototype method based on the results of interviews. Interviews were conducted as an evaluation of MIS using the PIECES Framework method involving 4 informants. The license design is made using the context diagram and the flow diagram data (DFD). The results of the evaluation with the PIECES Framework show that the MIS that is applied can provide convenience for users in managing drug supplies even though it has not been optimized and has not met the needs so that the MIS is feasible to be developed. Based on the results of the evaluation, it can be concluded that the application of MIS can help and facilitate pharmacists in carrying out their work by providing accurate and complete data and information as supporting data for the preparation of LPLPO, but it cannot be used to monitor expired date of drug and prepare automatic LPLPO.